2020
DOI: 10.1002/cac2.12104
|View full text |Cite|
|
Sign up to set email alerts
|

ZNF582 hypermethylation promotes metastasis of nasopharyngeal carcinoma by regulating the transcription of adhesion molecules Nectin‐3 and NRXN3

Abstract: Background Epigenetic regulation plays an important role in the development and progression of nasopharyngeal carcinoma (NPC). However, the epigenetic mechanisms underlying NPC metastasis remains poorly understood. We aimed to find functional genes which regulate the metastasis of NPC and identify therapeutic targets for NPC treatment. Methods Bisulfite pyrosequencing was used to analyze zinc finger protein 582 (ZNF582) methylation in NPC tissues and cell lines. Quantitative reverse transcription‐polymerase ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 54 publications
2
19
0
Order By: Relevance
“…Epstein–Barr virus (EBV), a large double-stranded DNA virus belonging to the γ-herpesvirus subfamily, causes latent infection of more than 95% of the adult population worldwide ( 1 , 2 ). As a widespread virus causing infectious mononucleosis during primary infection, EBV is also closely implicated in several malignancies in latent infection, including B-cell lymphomas, nasopharyngeal carcinoma (NPC) ( 3 , 4 , 5 ), EBV-associated gastric cancer, Burkitt's lymphoma, and Hodgkin's lymphoma ( 6 , 7 , 8 , 9 ). The viral oncogenic factors, such as RNA transcripts and proteins expressing during the latent or lytic phase have been reported to drive pathogenic processes ( 10 , 11 ).…”
mentioning
confidence: 99%
“…Epstein–Barr virus (EBV), a large double-stranded DNA virus belonging to the γ-herpesvirus subfamily, causes latent infection of more than 95% of the adult population worldwide ( 1 , 2 ). As a widespread virus causing infectious mononucleosis during primary infection, EBV is also closely implicated in several malignancies in latent infection, including B-cell lymphomas, nasopharyngeal carcinoma (NPC) ( 3 , 4 , 5 ), EBV-associated gastric cancer, Burkitt's lymphoma, and Hodgkin's lymphoma ( 6 , 7 , 8 , 9 ). The viral oncogenic factors, such as RNA transcripts and proteins expressing during the latent or lytic phase have been reported to drive pathogenic processes ( 10 , 11 ).…”
mentioning
confidence: 99%
“…Surprisingly, no DMCs were found in TP53. Among DMCcorrelated TF genes, some have been implicated in the progression of ESCC, including zinc finger genes such as ZNF382, ZNF582 and ZNF667 28,30,31 and Homeobox genes such as BARX1, HOXA13 and HOXC10. [32][33][34] All 7 CpG sites at the promoter of ZNF382, a NF-κB inhibitor frequently downregulated in ESCC, 28,35 were recurrently hyper-methylated in our data: at least one of the 7 DMCs were found in 75.82% (69/91) ESCC genomes.…”
Section: Resultsmentioning
confidence: 99%
“…A recent report has revealed that ZNF582 acts as a tumor suppressor gene in nasopharyngeal carcinoma (NPC) by regulating the transcription and expression of the adhesion molecules Nectin-3 and NRXN3 . Hypermethylation of ZNF582 promotes NPC metastasis via the regulation of these adhesion molecules [ 67 ]. The tumor suppressor role of ZNF582 was also observed in anal cancer and esophageal carcinoma, and its methylation seems to have potential as a cancer detection biomarker [ 68 , 69 ].…”
Section: Current Available Techniquesmentioning
confidence: 99%